PERENCANAAN STRATEGIK BERORIENTASI KEBERLANJUTAN BISNIS MENGGUNAKAN TRIPLE LAYER BUSINESS MODEL CANVAS STUDI KASUS: GHI TRAINING - Muhammad Sigit Susanto; Mukhamad Najib; Arry Ekananta (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Changes in the character of skills training customers towards the era of online learning due to the COVID19 pandemic have created a gap between business planning and reality. Therefore it is necessary to do intervene through strategic planning that considering stakeholder expectations as well as managing various factors that affect business sustainability. The aims of this study: (1) To identify strategic factors of business; (2) To formulate sustainable business development strategies. This research uses a descriptive approach through a case study at GHI Training during October and November 2020. Research data processing using IE matrix and TLBMC. Based on the evaluation results obtained 17 external strategic factors with an EFE score of 3,00 and 15 internal strategic factors with an IFE score of 2,87. The company is in a strong internal position and can respond well to opportunities and threats. Through the IE matrix, the company is placed in a hold and maintain position, so it is advisable to focus on the strategy of market penetration and product development. Essentially, from a theoretical and practical point of view, the use of TLBMC can help management to see comprehensively the company's business model and its relation to business sustainability. Keywords: strategic planning, business sustainability, COVID19, skill training, triple layer business model canvas